On the hydrogen-bond network and the non-Arrhenius transport properties of water. (10th November 2016) - Galamba, N
Abstract: We study the structural and dynamic transformations of SPC/E water with temperature, through molecular dynamics (MD), and discuss the non-Arrhenius behavior of the transport properties and orientational dynamics, and the magnitude of the breakdown of the Stokes–Einstein (SE) and the Stokes–Einstein–Debye (SED) relations, in the light of these transformations. Our results show that deviations from Arrhenius behavior of the self-diffusion at low temperatures cannot be exclusively explained by the reduction of water defects (interstitial waters) and the increase of the local tetrahedrality, thus, suggesting the importance of the slowdown of collective rearrangements. Interestingly we find that at high temperatures ( T ⩾ 340 K) water defects lead to a slight increase of the tetrahedrality and a decrease of the self-diffusion, opposite to water at low temperatures. The relative magnitude of the breakdown of the SE and the SED relations is found to be in accord with recent experiments (Dehaoui et al 2015 Proc. Natl Acad. Sci. USA 112 12020) resolving the discrepancy with previous MD results. Further, we show that SPC/E hydrogen-bond (HB) lifetimes deviate from Arrhenious behaviour at low temperatures in contrast with some previous MD studies. This deviation is nevertheless much smaller than that observed for the orientational dynamics and the transport properties of water, consistent with the relaxation times measured by several experimental methods. The HB acceptor exchange dynamics defined here by the acceptor switch and reform (librational dynamics) frequencies exhibit similar Arrhenius deviations, thus explaining to some extent the non-Arrhenius behavior of the transport properties and of the orientational dynamics of water. Our results also show that the fraction of HB switches through a bifurcated pathway follow a power law with the temperature decrease. Thus, at low temperatures HB acceptor switches are less frequent but occur on a faster time scale consistent with the temperature dependence of the ratio of the rotational relaxation times for the different Legendre polynomial ranks.